Malignant Peripheral Nerve Sheath Tumor di Regio Bahu yang menyerupai Undifferentiated Carcinoma: Tantangan Diagnostik - Handriyani, Fitri Nur; Tofrizal, Tofrizal; Mayorita, Pamelia (Fakultas Kedokteran Universitas Riau, 2025)
Malignant peripheral nerve sheath tumor (MPNST) is a rare and aggressive group of neoplasms arising from the peripheral nervous system sheath cells (Schwann cells or perineurial cells). Malignant peripheral nerve sheath tumors are typically seen in patients aged 20–50 years, and the most common sites are the trunk and extremities. This case highlights the diagnostic complexity and distinguishes MPNST from undifferentiated carcinoma. We present a case report of a 59-year-old male patient who presented with a rapidly growing mass in the right shoulder for six months. Clinical examination on his shoulder showed a solid mass, lobulated and ulcerated, and an irregular margin measuring 16x12x5 cm. A thoracic MRI revealed a large mass, fusiform and lobulated, with dimensions of 15.02 x 15.81 x 12.65 cm. The patient underwent surgical incision biopsy of the mass. Histopathological and immunohistochemical examinations with S100 and cytokeratin (CK) markers were performed on this patient with MPNST results. The immunoprofile of MPNST showed focal positive staining for S100 marker and negative staining for CK marker. The diagnosis of malignant peripheral nerve sheath tumor can be more challenging if the histopathological examination resembles a feature of undifferentiated carcinoma, like lobulated pattern and clustering of cells with round-oval nuclei. The role of immunohistochemical examination is very important to rule out differential diagnoses.